Application of spatially hybrid fluid–kinetic neutral model on JET L-mode plasmas. (June 2021) - Horsten, N.; Groth, M.; Blommaert, M.; Dekeyser, W.; Pérez, I. Paradela; Wiesen, S.; ,
Abstract: We present a spatially hybrid fluid–kinetic neutral model that consists of a fluid model for the hydrogen atoms in the plasma grid region coupled to a kinetic model for atoms sampled at the plasma–void interfaces and a fully kinetic model for the hydrogen molecules. The atoms resulting from molecular dissociation are either treated kinetically (approach 1) or are incorporated in the fluid model (approach 2). For a low-density JET L-mode case, the hybrid method reduces the maximum fluid–kinetic discrepancies for the divertor strike-point electron densities and electron temperatures from approximately 150% to approximately 20% for approach 1 and to approximately 40% for approach 2. Although the simulations with purely fluid neutral model become more accurate for increasing upstream plasma density, we still observe a significant improvement by using the hybrid approach. When consuming the same CPU time in averaging the electron strike-point densities and temperatures over multiple iterations as for the simulations with fully kinetic neutrals, hybrid approach 1 reduces the statistical error with on average a factor 2.5. Hybrid approach 2 further increases this factor to approximately 3.3, at the expense of accuracy. Highlights: For atoms, a fluid model is coupled to a kinetic model in the void regions. Molecules are treated kinetically in the whole domain. The hybrid approach significantly reduces the target fluid–kinetic discrepancies. Compared to fully kinetic neutrals, a 2-4 statistical error reduction is obtained.